2016
DOI: 10.1590/s0100-204x2016000200008
|View full text |Cite
|
Sign up to set email alerts
|

Duração das alterações em propriedades físico-hídricas de Latossolo argiloso decorrentes da escarificação mecânica

Abstract: Resumo -O objetivo deste trabalho foi determinar o tempo de duração do efeito da descompactação do solo, por escarificação mecânica, por meio de indicadores físico-hídricos de Latossolo argiloso, manejado em sistema plantio direto (SPD). Os tratamentos consistiram em meses (0, 6, 12, 18, 24, 30 e 36) transcorridos após escarificação mecânica em SPD e em testemunha sem escarificação em SPD há 27 anos. Foram avaliadas as variáveis: resistência mecânica à penetração, taxa de infiltração de água no solo, densidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 18 publications
0
45
0
13
Order By: Relevance
“…At 70 days after sowing (02/04/2015), Bd was lower and Ma was higher in CHR, but only in the 0.10-0.20 m layer, also with no difference for CH. The absence of differences in the first layer 70 days after sowing indicates that rainfall (Figure 1) caused soil reconsolidation, which commonly occurs in a period of less than a year, even in highland clayey soils (Drescher et al, 2016). Although reduction in the initial degree of compaction from chiseling remained for a short period, its effect on the transpiration reduction factor was more noticeable, as will be discussed later.…”
Section: Results and Dicussionmentioning
confidence: 93%
“…At 70 days after sowing (02/04/2015), Bd was lower and Ma was higher in CHR, but only in the 0.10-0.20 m layer, also with no difference for CH. The absence of differences in the first layer 70 days after sowing indicates that rainfall (Figure 1) caused soil reconsolidation, which commonly occurs in a period of less than a year, even in highland clayey soils (Drescher et al, 2016). Although reduction in the initial degree of compaction from chiseling remained for a short period, its effect on the transpiration reduction factor was more noticeable, as will be discussed later.…”
Section: Results and Dicussionmentioning
confidence: 93%
“…crops during winter. Drescher et al (2016) observed that, after mechanical scarification in an Oxisol, the changes in the properties indicative of soil structure, such as density, total porosity, and macroporosity, lasted less than a crop season, but that the effects of scarification were maintained for up to 24 months for properties related to water transport, including hydraulic conductivity and stable infiltration rate of water in the soil; therefore, these indicators are more sensitive for evaluating the duration of mechanical decompression. Moreover, Nunes et al (2014) reported that, in an Ultisol, the positive effects of scarification on soil density and degree of compaction did not last for more than 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…Na profundidade de 0,07 a 0,15 m os tratamentos utilizados para produção de grãos ILP, PD, SPD e TR apresentaram maior densidade. Esse comportamento pode ser explicado pelo acúmulo das tensões impostas pelo tráfego de máquinas agrícolas, sendo essa camada reconhecida como a camada de maior restrição ao crescimento radicular das plantas em áreas manejadas sob SPD conforme verificado também por (Secco et al 2009;Drescher et al 2016). Nesse sentido, cabe ressaltar ainda que ao considerar a proposição de densidade crítica de 1,30 a 1,40 Mg m -3 para solos argilosos O tratamento TR apresenta densidade do solo com características tanto de CN, quanto de lavoura, possibilitando observar que após dois anos de manejo o TR encontra-se em fase de transição entre os dois sistemas produtivos.…”
Section: Resultsunclassified
“…A perda da qualidade física do solo através da compactação, tem sido considerada como um dos principais fatores responsáveis pela queda da produtividade das culturas agrícolas (Klein et al, 2009). A intensificação do processo de compactação está associada diretamente ao sistema de manejo do solo adotado (Drescher et al, 2016), aliado às práticas agrícolas não conservacionistas que provocam alterações em sua estrutura. A resistência mecânica do solo à penetração, juntamente com a distribuição do espaço poroso, são atributos físicos do solo que podem limitar o crescimento do sistema radicular e a produtividade das culturas (Oliveira et al, 2015), uma vez que, influenciam as condições de crescimento e aeração do sistema radicular, infiltração e disponibilidade de água para as plantas .…”
Section: Referênciasunclassified